Morfometria geometrica non invasiva: studio della forma dei semi archeologici di vite per risalire all'origine d'antiche varietà antropiche - Milanesi, Claudio; Antonucci, Francesca; Lorenzo, Costantini; Menesatti, Paolo; Costa, Corrado; faleri, Claudia; Vignani, Rita; Cresti, Mauro (Archeomatica, 2013)
The purpose of this paper is to describe a non-invasive and quantitative imaging analysis method based on elliptic Fourier. Archaeological seeds reduction in size, respect the contemporary fresh seeds used as control, was evaluated to obtain admissible morphometric data. Investigations established different morphological variations between grape seeds ancient cultivars.